Cellular and cytokine immunoregulation in patients with chronic obstructive pulmonary disease and bronchial asthma - Wanda Stankiewicz; Marek P. Dabrowski; Andrzej Chcialowski; Tadeusz Plusa (Mediators of Inflammation)
Background: Different forms of chronic airway inflammation may involve diverse pathogenic elements. In general, deficient defence response is a feature of chronic obstructive pulmonary disease (COPD), whereas distorted immunoregulatory mechanisms lead to development of asthmatic symptoms. In addition to diverse effector mechanisms, the cellular and humoral elements participating in the development of immune response may appear to be different in COPD and bronchial asthma (BA) patients.